(untitled) (Faridpur Medical College Journal, 2016)
Emergency obstetric hysterectomy is removal of part or whole of the uterus done to save the life of a mother in complications in the intra partum or post-partum period. This study was done to assess the cases of emergency obstetric hysterectomy (EOH) in view to find out the indications, the patient profile, the risk factors, the morbidity and mortality associated with the procedure. It was a retrospective analysis of 40 cases of obstetric hysterectomy performed in Faridpur Medical College Hospital (FMCH) during the period of August 2012 to July 2014. Patients were evaluated from history and clinical observation records regarding maternal age, parity, indication of operation, associated risk factors, surgical procedure and complications during hospital stay. In maximum patient with EOH the overall incidence is in the age group of 25-29 years (42.5%) and parity of 2nd-3rd. The most common complication was ruptured uterus 50% and PPH 12.5%. Among the risk factors the most common was previous caesarean section (55%) then grand multipara (15%). Out of 40 cases 40% needed total hysterectomy and 60% was managed by subtotal hysterectomy. In most cases complications were hemorrhage and 100% patient needed blood transfusion among which 50% in the post-operative period. All the patients were discharged after treatment with no history of maternal death or referral to higher centers. Emergency obstetric hysterectomy is a lifesaving procedure when decision is taken at proper time, done rapidly by expert surgeon along with availability of blood and safe anesthesia. Thus it can play a vital role to reduce and prevent maternal death. Faridpur Med. Coll. J. Jan 2016;11(1): 2-5